Advances in non-hormonal pharmacotherapy for the treatment of male infertility: the role of inositols. (13th June 2022) - Condorelli, Rosita A.; Cannarella, Rossella; Crafa, Andrea; Barbagallo, Federica; Gusmano, Carmelo; Avola, Ottavia; Mongioì, Laura M; Basile, Livia; Calogero, Aldo E.; La Vignera, Sandro
ABSTRACT: Introduction: Several antioxidants are available for the treatment of male infertility. Although the benefit of myo-inositol (MYO) and D-chiro-inositol (DCI) for female infertility is recognized, their role in male infertility is a matter of debate. Areas covered: The authors review the impact that treatment with MYO and/or DCI may have on conventional and bio-functional sperm parameters [mitochondrial membrane potential (MMP), sperm chromatin compactness, and sperm DNA fragmentation (SDF)], seminal oxidative stress (OS), and pregnancy, miscarriage, and live birth rates, and the possible mechanisms involved. Furthermore, the authors gather evidence on the effects of MYO and/or DCI on sperm function in vitro . Expert opinion: MYO can improve sperm count, motility, capacitation, acrosome reaction, and MMP. No data are currently available on the effects of DCI in vivo . Both MYO and DCI ameliorate sperm motility and MMP in vitro . Therefore, the use of inositols should be preferred in patients with idiopathic asthenozoospermia, especially in case of impaired sperm mitochondrial function. Due to their insulin-sensitizing action, a role for these molecules may be envisaged for the treatment of infertility caused by carbohydrate metabolism derangement.